1998
DOI: 10.1080/0950069980200802
|View full text |Cite
|
Sign up to set email alerts
|

The nature of students’ informal science conceptions

Abstract: Case studies have been constructed of primary school children's developing explanations of a range of air pressure phenomena. A range of conceptions relating to air pressure have been identified, and insights gained concerning the way these interrelate over time and over context. It was found that children are naturally generative in their construction of explanations, but that they use conceptions in quite complex and fluid ways. It is argued that naive conceptions maintain a valuable function as intuitive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 29 publications
2
38
0
11
Order By: Relevance
“…Children would hold both ideas at the same time, as multiple perspectives (Tytler, 1994(Tytler, , 1998a, and on occasions explicitly voiced this as a characteristic of their thinking. Previous claims in the literature (e.g., Bar & Galili, 1994) that these different displacement conceptions represent different developmental stages, do not seem to be supported by these findings.…”
Section: Location and Languagementioning
confidence: 98%
“…Children would hold both ideas at the same time, as multiple perspectives (Tytler, 1994(Tytler, , 1998a, and on occasions explicitly voiced this as a characteristic of their thinking. Previous claims in the literature (e.g., Bar & Galili, 1994) that these different displacement conceptions represent different developmental stages, do not seem to be supported by these findings.…”
Section: Location and Languagementioning
confidence: 98%
“…Driver & Easley, 1978;Driver, Guesne & Tiberghien, 1985;Vosniadou, 1992;de Posoda 1997;Tytler 1998;Taber, 1995aTaber, , 2000. The tenacious nature of such 'alternative frameworks' was emphasised by those researchers who first brought 'children's science' to wide notice (e.g.…”
Section: The Stability Of Student Thinkingmentioning
confidence: 99%
“…Thus, Tytler (1998) found that students were extremely fluid in their reasoning and inconsistent in their application of conceptions in different contexts. Welzel and Roth (1998) demonstrated that students' reasoning changed significantly even during a single interview, for example, in relation to contextual factors such as the complexity of the questions asked.…”
Section: Introductionmentioning
confidence: 99%
“…In a case study of one student, Taber (1995) demonstrated that the student's alternative framework about charges acted as a block to learning about chemical bonding. Some studies suggest that such "blocks" or "obstacles" to learning need to be weakened or even abandoned before a new conception can develop (De Posada, 1997;Hewson & Thorley, 1989), and that such conceptual change requires rational considerations on the part of the learner (Carey, 1999;Strike 1 Different authors have used different labels for such nonscientific ideas, implicating different assumptions about their nature and properties (Smith et al, 1993;Tytler, 1998). Here, we will use the term "misconception" in a general sense, without any particular connotations, and interchangeably with "nonscientific idea," in agreement with several other authors (Nicoll, 2001;Smith et al, 1993;Özmen, 2004).…”
Section: Introductionmentioning
confidence: 99%